Oilseed warehouse location selection with an integrated approach: a case of Turkey - Gergin, Ramazan Eyup; Peker, Iskender; Baki, Birdogan; Tuzkaya, Umut Rifat; Tanyas, Mehmet (EMERALD GROUP PUBLISHING LTD, 2023)
Purpose Agricultural sector not only meets the nutritional requirements of all living creatures but also generates the primary source of the raw material provided by various branches of industry to fulfill their functions. It is of great importance to increase studies on oilseeds which have an important role in Turkey's agricultural products. They are grown in almost all of the country, which are vital for the nutrition and many sectors. The main purpose of the study is to offer an integrated approach to determine potential warehouse locations for oilseeds. Design/methodology/approach This is the first study that integrates Delphi, analytical hierarchical process (AHP), technique for order preference by similarity to ideal solution (TOPSIS), P-Median and Panel data analysis in a real case. This integrated approach consists of the following steps, respectively: (1) The criteria were determined by the Delphi method. (2) The weights of the criteria were calculated by AHP and the provinces with the highest oilseed warehouse potential in seven regions of Turkey were specified by TOPSIS. (3) Oilseed warehouse numbers and locations were obtained by P-Median. (4) In order to answer whether the distribution network is profitable in the future with the determined center locations, a forecast model based on panel data analysis was created. (5) Regional representatives were determined for 2030, and the distribution network was analyzed again. (6) The costs that arose in 2018 and 2030 were computed and compared by cost analysis. (7) The effect of the change in criteria weights on the alternative results was tested by scenario analysis. Findings The findings indicated that oilseed crop production potential and oilseed crop production area turned out to be the most important criteria. Furthermore, the results showed that this model is robust and suitable for warehouse location selection studies. Practical implications The study can serve as a guide for local and central policy makers with both the criteria it uses and the model it develops. Originality/value The main contribution of this study is that the integrated approach has been used for the first time in location selection in a real case.
Keywords: Agricultural sector; Delphi; MCDM; Oilseed; P-Median; Panel data analysis; Warehouse location selection; INTERNATIONAL DISTRIBUTION CENTER; DECISION-MAKING; DISTRIBUTION CENTERS; MODEL; NETWORK; SUPPORT; PRODUCT; SEARCH; MARKET; Computer Science